2019
DOI: 10.1186/s12893-019-0569-6
|View full text |Cite
|
Sign up to set email alerts
|

Incisional hernia recurrence after open elective repair: expertise in abdominal wall surgery matters

Abstract: Background Recurrence after incisional hernia repair is one of the major problems related with this operation. Our objective is to analyze the influence of abdominal wall surgery expertise in the results of the open elective repair of incisional hernia. Methods We have compiled the data of a cohort of patients who received surgery for an incisional hernia from July 2012 to December 2015 in a University Hospital. Data were collected prospectively and registered in the Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…When the operations were performed in an AWU, there were fewer complications (66.7% vs. 28.6%; P = 0.04). These data confirm the risks of urgent IH surgery [24] and support the hypothesis that these techniques should be performed, if possible, by specialized surgeons [13] or should be avoided, particularly in higher risk situations, such as emergencies.…”
Section: Discussionsupporting
confidence: 83%
“…When the operations were performed in an AWU, there were fewer complications (66.7% vs. 28.6%; P = 0.04). These data confirm the risks of urgent IH surgery [24] and support the hypothesis that these techniques should be performed, if possible, by specialized surgeons [13] or should be avoided, particularly in higher risk situations, such as emergencies.…”
Section: Discussionsupporting
confidence: 83%
“…The second biggest influence is the prices of the mesh (β = −0.500, p < 0.001). This fits in with the increased complexity of these hernias and their care as described in the literature, as well as the increased complication rate compared to primary ventral hernias [ 4 , 33 , 34 , 35 , 40 , 41 ]. The epidemiological factor BMI (β = −0.590, p < 0.001), as well as non-modifiable epidemiological factors such as gender (β = −0.113, p = 0.055) and age (β = −0.026) also have a major influence ( p < 0.050).…”
Section: Discussionsupporting
confidence: 55%
“…The complication rate for primary ventral hernia care is displayed as 3–23% [ 29 , 30 , 31 , 32 ]. The rate of complications in incisional hernia care is presented as 12.7–29.1% [ 33 , 34 , 35 ]. These data show that ventral hernia repair is an important surgical issue.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that patients treated by surgeons who have specialized training and clinical practice focused on abdominal wall reconstruction [ 14 ], or those who perform high volumes of incisional hernia surgery [ 15 ], have better outcomes compared to other patients. These improved results may be due to more appropriate choice of procedures and/or mesh materials, better surgical technique or a combination of both.…”
Section: Discussionmentioning
confidence: 99%